Urgensi Lembaga Pelindungan Data Pribadi di Indonesia Berdasarkan Asas Hukum Responsif - Erlyns Yolanda; Rugun Romaida Hutabarat (Syntax Corporation, 2023)
These days, crimes against personal data are not uncommon in society, necessitating a legal foundation to provide legal protection for individuals' privacy rights. The enactment of the Personal Data Protection Act brings a breath of fresh air to the community, but its comprehensive implementation is still not possible due to the absence of an authorized institution under this law. This research aims to discuss the importance of a personal data protection institution in ensuring the security of individuals' personal data. The study is of a normative nature and employs a statutory approach and a historical approach. The research findings indicate that the substantive provisions of the personal data protection law have sufficiently addressed the need for personal data protection for the community. However, these regulations have not been fully implemented due to the lack of a clearly defined institution in the law, resulting in delays in the establishment of such an institution. Therefore, it is necessary to have regulations that govern the inclusion of a supporting state institution in a law, in order to establish the desired standardization and avoid a lack of provisions that impede the formation of the institution